Implementation of Effective Communication by Midwives in Increasing Patient Compliance in Carrying out Antenatal Care: Penerapan Komunikasi Efektif Bidan dalam Peningkatan Kepatuhan Pasien Melaksanakan Antenatal Care - Ardhiangtyas, Nisa; Mufida Dian Hardika; Ajeng Novita Sari; Siti Nur Fadilah (Prodi Kebidanan Universitas Islam Negeri Alauddin Makassar, 2024)
Introduction Communication is a very important tool in fostering a therapeutic relationship between health workers and patients which can influence the quality of health care services. Therapeutic communication is very important because it can influence the level of patient satisfaction with the health services provided. All behavior and health information provided by midwives must be therapeutic for the patient. Therapeutic communication also develops interpersonal relationships between patients and midwives, where midwives have special skills and must pay attention to every non-verbal interaction and behavior. Good therapeutic communication will lead to patient satisfaction, which ultimately influences patient compliance with the pregnancy check-up schedule. Methode Analytical correlation research, with a total research sample of 25 people. The sampling technique uses simple random sampling. Research data was analyzed using SPSS starting from univariate analysis to describe each research variable, then bivariate analysis to analyze the relationship between the independent variable and the dependent variable using the Spearman rank formula. The results of the Spearman correlation test via SPSS showed that the Spearman correlation coefficient (rs) = 0.320 with a 2 tailed sig value (p) = 0.005 where p < 0.05 so that H1 was accepted, meaning there was a relationship between the variables in this study. Conclusion There is a relationship between effective communication and patient compliance in carrying out pregnancy checks according to schedule.